1995
DOI: 10.1200/jco.1995.13.8.1933
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of skin cancer and reduction of keratotic skin lesions during acitretin therapy in renal transplant recipients: a double-blind, placebo-controlled study.

Abstract: Acitretin 30 mg/d over 6 months had significantly more effect than placebo in the prevention of squamous cell carcinomas and reduced the occurrence of keratotic skin lesions in a group of renal transplant recipients with severe lesions. This effect was most pronounced in patients with a history of squamous cell carcinomas and basal cell carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
244
3
4

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(257 citation statements)
references
References 17 publications
6
244
3
4
Order By: Relevance
“…Keratotic lesions increased by 28% in the placebo group and decreased by 13AE4% in the acitretin group. 52 The third study which compared different doses of acitretin did not show a difference in tumour rate between doses of 0AE4 mg kg )1 daily and 0AE4 mg kg )1 daily reducing to 0AE2 mg kg )1 for 9 months, nor a significant reduction compared with that observed in the preceding year without acitretin. 53 However, thickness of lesions was reduced and numbers of actinic keratoses were reduced.…”
mentioning
confidence: 99%
“…Keratotic lesions increased by 28% in the placebo group and decreased by 13AE4% in the acitretin group. 52 The third study which compared different doses of acitretin did not show a difference in tumour rate between doses of 0AE4 mg kg )1 daily and 0AE4 mg kg )1 daily reducing to 0AE2 mg kg )1 for 9 months, nor a significant reduction compared with that observed in the preceding year without acitretin. 53 However, thickness of lesions was reduced and numbers of actinic keratoses were reduced.…”
mentioning
confidence: 99%
“…Most of these trials focus on individuals at an increased risk of developing cancer, such as patients with pre-malignant lesions or patients who have been successfully treated for an early-stage carcinoma and have a high risk of developing a second primary cancer. The use of retinoids in patients with cutaneous actinic keratoses results in a significant decrease in the incidence of squamous cell carcinomas of the skin (Moon et al, 1997), and this is also observed in renal transplant patients with this pre-malignant condition (Bavinck et al, 1995;Rook et al, 1995). Similarly, topical ATRA can lead to a clinical and histological improvement in patients with the dysplastic nervous syndrome (Edwards and Jaffe, 1990;Halpern et al, 1994).…”
Section: Clinical Datamentioning
confidence: 95%
“…43 When confronted with perpetual development of cutaneous carcinomas, prophylactic systemic retinoids, derivatives of vitamin A, should be considered. [45][46][47] These agents, although not approved by the Food and Drug Administration for this indication, have potent prodifferentiation and tumor-suppressive effects. Unfortunately, systemic retinoids only suppress tumor development, not active skin cancers.…”
Section: Management Of Skin Cancer In Organ-transplant Recipientsmentioning
confidence: 99%
“…Acetretin, the most commonly used systemic retinoid, is administered orally at 25 mg/d, is usually well tolerated, and has not been shown to increase the risk for rejection. 46 Newer experimental retinoids may have a better side-effect profile and be tolerated as a chemopreventative agent for long durations. Monitoring serum lipid levels, hepatic function, and immunosuppressant levels is recommended when administering oral retinoids.…”
Section: Management Of Skin Cancer In Organ-transplant Recipientsmentioning
confidence: 99%
See 1 more Smart Citation